Risk Analysis And Recommendations To Improve The Logistics Cost Performance Of The EPC Project At Remote Area - Firdausy, Ferdi (Journal Research of Social Science, Economics, and Management, 2023)
The EPC and construction projects generally have a high level of complexity, and uncertainty. The changes that have occurred in the engineering, construction, control systems, and sub-logistics stages will impact logistics cost performance and finally affect the project margins, weak of project control, and high risk. The purpose of this study is to determine the variable risk that affects the performance of logistics costs, to obtain high-risk identification of engineering, construction, and system control variables that affect the performance of logistics costs and to determine the risk responses and recommendations to improve logistics cost performance on EPC projects in remote locations. Data was collected from literature studies, interviews with respondents, and experts. By 51 respondents' answers, the risk was identified are 30 factors in terms of the probabilities and impact. The method through descriptive analysis, validity & reliability testing, and qualitative risk analysis. Further, the follow-up of risk results would carry out through proactive and reactive mitigation. This research found 7% of the variables were extreme, and 93% were high-risk categories. Thus it indicates that all variables affect the logistics costs performance where the remote project locations are one of the main factors in increasing the logistics costs.